The Potential of Single Garlic Oil in Inhibiting The Growth and Damaging The Membrane of Pseudomonas aeruginosa Bacteria - Sri Rahayu Lestari; Agung Witjoro; Soeyati Poejiani (Universitas Gadjah Mada, 2018)
Nosocomial infection caused by Pseudomonas aeruginosa bacteria is hard to be treated since the infection transmission is fast and it is resistance to the antibiotic. Antibiotic resistance in the bacteria can be treated with various natural ingredients from plants and one of the plants is single garlic. Single garlic contains organosulfur compounds in form of alliin, allicin, and ajoene. This research aimed to analyze the potential of single garlic oil (SGO) in inhibiting the growth and the damage of membrane of P. aeruginosa bacteria in in vitro with disc diffusion method by giving treatments of essential oil extract in concentration of 25 mg/ml, 50 mg/ml, 75 mg/ml and 100 mg/ml, and 1% dimethylsulfoxide (DMSO) as the negative control and Ceftazidimeof 30 µg/ml as the positive control. The damage of the bacterial cell membrane was observed with Scanning Electron Microscopy (SEM) with a magnification of 25000X. The result of the measurement of the zone of inhibition was analyzed using one-way ANOVA. The research results indicate that SGO could inhibit the growth of P. aeruginosa bacteria with strong criteria, which was in a concentration of 100 mg/ml.